Caffeine and Exercise Performance: Possible Directions for Definitive Findings - Martins, Gabriel Loureiro; Guilherme, João Paulo Limongi França; Ferreira, Luis Henrique Boiko; de Souza-Junior, Tácito Pessoa; Lancha, Antonio Herbert (Frontiers in Sports and Active Living, 2020)
Caffeine is one of the most studied supplements in the world. Studies correlate its use to increased exercise performance in endurance activities, as well as its possible ergogenic effects for both intermittent and strength activities. Recent findings show that caffeine may increase or decrease exercise performance. These antagonist responses may occur even when using the same dosage and for individuals with the same characteristics, making it challenging to explain caffeine's impact and applicability. This review article provides an analytic look at studies involving the use of caffeine for human physical performance and addresses factors that could influence the ergogenic effects of caffeine on different proposed activities. These factors subdivide into caffeine effects, daily habits, physiological factors, and genetic factors. Each variable has been focused on by discussions to research related to caffeine. A better understanding and control of these variables should be considered in future research into personalized nutritional strategies.